Innovative Strategies in Agricultural Land Management Owned by the KSB Agriculture Office to Increase Regional Original Income - Dedi Suryadi; Muammar Khadafie (Manunggal Halim Jaya, 2026)
State-owned agricultural land serves as a strategic asset for local governments in enhancing local revenue (PAD). Nevertheless, empirical investigations that connect innovative land management strategies with the optimization of PAD remain scarce in Indonesia. This study seeks to identify and analyze innovative strategies employed in the management of agricultural land by the West Sumbawa Regency Agriculture Office (KSB) and evaluate their contribution to PAD. A descriptive qualitative research design was employed, utilizing purposive sampling techniques across five strategic agricultural locations. Data collection was conducted through semi-structured interviews, field observations, and document analysis of PAD reports from 2019 to 2023. Thematic analysis was performed using NVivo, with triangulation employed to ensure validity. Three principal strategies were identified: (1) the adoption of high-productivity drought-tolerant varieties (VUB) and drip irrigation, which increased rice productivity by 18%; (2) crop diversification incorporating horticulture, which enhanced agricultural net income by 25%; and (3) public-private partnership marketing, which stabilized commodity prices and reduced income volatility. These innovative land management strategies significantly contribute to the growth of PAD in KSB. The findings provide a replicable model for other regions, with implications for sustainable agricultural policies and local economic development.